2014
DOI: 10.4238/2014.march.12.10
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate-induced-1 gene from Eucalyptus (EgPHI-1) enhances osmotic stress tolerance in transgenic tobacco

Abstract: ABSTRACT. Environmental stresses such as drought, freezing, and high salinity induce osmotic stress in plant cells. The plant response to osmotic stress involves a number of physiological and developmental changes, which are made possible, in part, by the modulation of the expression of specific genes. Phosphate-induced-1 gene (PHI-1) was first isolated from phosphate-treated phosphate-starved tobacco cell cultures as a stress-inducible gene, which is presumably related to intracellular pH maintenance; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The phi-1 gene was later on found to be homologous to the A. thaliana EXORDIUM gene which is expressed in proliferating cells ( Ferrar et al, 2003 ). A more recent study has shown that the overexpression of the Eucalyptus globulus EgPHI-1 gene enhances the tolerance of transgenic tobacco plants to osmotic stress ( Sousa et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The phi-1 gene was later on found to be homologous to the A. thaliana EXORDIUM gene which is expressed in proliferating cells ( Ferrar et al, 2003 ). A more recent study has shown that the overexpression of the Eucalyptus globulus EgPHI-1 gene enhances the tolerance of transgenic tobacco plants to osmotic stress ( Sousa et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The phi proteins have been identified for the first time in tobacco cell suspension cultures deprived of phosphate, but their role has not been demonstrated . Recently, the EgPHI‐1 protein of Eucalyptus has been shown to increase the osmotic stress tolerance . Finally, the ribonucleases T2 were assumed to contribute to phosphate remobilization from nucleic acids .…”
Section: Discussionmentioning
confidence: 99%
“…erg1 is a potato PHI-1-Like gene involved in ethylene and salicylic acid pathways ( Dellagi et al, 2000 ). Overexpression of EgPHI-1 significantly increased tolerance to NaCl, PEG, and mannitol treatments ( Sousa et al, 2014 ). At present, there are very few papers reporting studies on EXO genes, and the functions of EXO proteins are unclear, particularly in cotton.…”
Section: Introductionmentioning
confidence: 99%